WHICH SECTORS TO STIMULATE FIRST IN BRAZIL? ESTIMATING THE SECTORAL POWER TO PULL THE ECONOMY OUT OF THE RECESSION - Morrone, Henrique (Investigación Económica, 2018)
The current recession in Brazil has provoked intense discussion concerning ways to boost economic activity. This paper intends to contribute to the debate by ranking the sectors that have the power to pull the economy out of the recession when they are stimulated, employing the eigenvector method developed by Dietzenbacher (1992). To that end, we first estimated the input-output (I-O) matrix for 2013 applying Guilhoto and Sesso (2005)’s methodology and build an I-O matrix from the National Statistical Accounts. Later, we employed the eigenvector method to find the inter-sector backward linkages and ranked them. The results highlight the importance of petroleum refining and coke, resin manufacturing and elastomers, various chemical products and preparations, and chemicals to boost the recovery of the economy. Nonetheless, the traditional sectors of construction and automotive manufacturing exhibited poor and modest results respectively.